EFEKTIFITAS EKSTRAK METANOL DAUN KARI (Murraya koeginii) DAN CABAI JAWA (Piper retrofractum) TERHADAP LARVA Crocidolomia pavonana zell - Maulina, Faza; Bahri, Syamsul; Heviyanti, Maria (University of Prof. Dr. Hazairin, SH, 2023)
The use of chemical pesticides at the level of vegetable farmers is indicated in excessive amounts, while this is very dangerous for both the environment and humans. Chemical pesticides can pollute the environment because they are toxic and overused. Curry leaves (Murrayakoeginii) and Javanese chili (Piper retrofractum) can kill larvae, are safe for animals, and safe for the environment. Objective: To determine the effectiveness of methanol extract of curry leaves (Murraya koeginii) and Javanese chili (Piper retrofractum) against Crocidolomia pavonana Zell larvae. Research method: using a completely randomized design (CRD) with a factorial pattern consisting of two factors, namely the extraction material factor (I) consisting of 2 levels, namely I1 = Javanese Chilli Extract, I2 = Curry Leaf Extract. Furthermore, the extract concentration factor (K) which consists of five levels. The concentration of the extract was determined based on the results of preliminary testing of the test larvae which could cause 15% and 50% mortality of the larvae. Thus, 10 treatment combinations were obtained, each treatment was repeated 3 times, so there were 30 experimental units. In each petri dish, 10 C. pavonana larvae will be introduced, so that the total number of petri dishes is 30 plates along with 300 C.pavonana imago and all of them are observed. Results: Statistical analysis found that to control C. pavonana larvae, Java chili (Piper retrofractum) extract (I1) with a concentration of 0.35% (K1) could be used.